Digital Business Transformation and Business Resilience: The Moderating Role of Perceived Organizational Support in the Hospitality Emerging Business Economy - Friday Ogbu Edeh; Neji Desmond Oben; Blessing Friday Edeh; Lilian Asinai; Kibuuka Muhammad (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
Hospitality businesses in emerging economies have adopted digital tools to improve service delivery, customer satisfaction, and stakeholder trust, prompting scholars to conduct empirical research to strengthen their resilience, particularly in Nigeria. This research investigated the effect of digital business transformation (DBT) on business resilience in an emerging business economy with perceived organizational support (POS) as a moderating role using a cross-sectional survey. The study focused on workers from selected hospitality businesses in Abakaliki, southeastern Nigeria, using simple random sampling to choose the businesses. Participants' demographics were analyzed with frequency distribution, and research hypotheses were tested using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The study revealed that POS provides resources that moderate the effect of DBT on business resilience. Consequently, the study recommends that the management of hospitality firms should focus on DBT to help the firms to be resilient. This can be achieved through using digital tools, knowledge, skills, and processes to improve the turbulence-handling capability of the firm.